(untitled) (Bangladesh Journal of Plant Taxonomy, 2013)
Pollen grains of 40 taxa of Rhododendron L. and its closely related genera, Therorhodion L. and Menziesia Sm., were examined by means of light microscopy and scanning electron microscopy (SEM), or SEM alone. Pollen tetrads of R. japonicum, R. schlippenbachii, R. tsusiophyllum and M. pentandra were examined also withtransmission electron microscopy. In all the genera studied, 3-colporate, oblate tosuboblate pollen grains are arranged in tetrahedral tetrads. The apocolpial pollen wall is composed of the exine - well developed tectum, columellae, foot layer and endexine, and the intine. On the contrary, the septal exine is composed of fragmentary tectum, and the two foot layers of adjacent grains are sometimes connected by columellae and endexine. Among different infrageneric taxa only the subsect. Ledum (sect. & subgen. Rhododendron) was characterized by small sized pollen tetrads, higher 2f/D value and rugulate exine sculpture. The pollen morphological characteristics overlapped each other in all other taxa. Thus palynological features showed little usefulness in the infrageneric classification of Rhododendron, however, they gave additional support to the individualgeneric status of Menziesia and Tsusiophyllum, and the sister relationship between Rhododendron and Therorhodion. DOI: http://dx.doi.org/10.3329/bjpt.v20i2.17393 Bangladesh J. Plant Taxon. 20(2): 185-199, 2013